2017
DOI: 10.1007/s00432-017-2419-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel classification scheme for advanced laryngeal cancer midline involvement: implications for the contralateral neck

Abstract: As a consequence, for type A category, a contralateral neck dissection might be avoidable accompanied by a reduction in surgical complications and operating time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Several previous studies have demonstrated the pN stage as a prognostic predictor and an efficient indicator for adjuvant therapy, which is mainly based on the number of metastatic lymph nodes and extra‐nodal extension (ENE) . However, a sufficient number of the examined lymph node is key to ensure the precise nodal staging.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated the pN stage as a prognostic predictor and an efficient indicator for adjuvant therapy, which is mainly based on the number of metastatic lymph nodes and extra‐nodal extension (ENE) . However, a sufficient number of the examined lymph node is key to ensure the precise nodal staging.…”
Section: Introductionmentioning
confidence: 99%
“…Backes et al [3] described insufficient surgical margins as one of the main risks for reduced overall and recurrence-free survival of laryngeal cancer patients. Böttcher et al [7] retrospectively analyzed 58 locally advanced staged laryngeal cancers following laryngectomy (LE). They described the importance of midline involvement in preoperative CT scans and a 100% risk reduction without midline involvement for contralateral lymph node metastases.…”
Section: Introductionmentioning
confidence: 99%
“…They described the importance of midline involvement in preoperative CT scans and a 100% risk reduction without midline involvement for contralateral lymph node metastases. They considered contralateral elective ND as avoidable in locally advanced laryngeal carcinomas without midline involvement [7]. Oztürkcan et al [28] described a higher risk for contralateral metastases in patients with ipsilateral lymph node invasion with and without extracapsular spread.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations